O "fardo" da velhice e do envelhecimento: subjetividades e políticas públicas no Brasil - Aidar, Maria Aura Marques (2014)
In the burden of the oldness and aging: subjectivities and public politics in Brazil, we studied the aspects related to the elderly as subjects from the present time. It is analyzed in this paper, the subjectivity of being elder, the multiplicity of this condition, the difficulty of categorization of the oldness as a social problem. The increase of life expectancy has been considered an obstacle to the public account. We started from this analysis in order to discuss the Welfare State, an institution created to support workers at illness, oldness, and death but then used for financing the nation, what resulted in economical difficulties to the entity. The insufficient amount of benefits for a worthy life, and the lack of support that the elders are submitted, generate the necessity of public politics. The United Nations, in its search for the human rights respect and social progress, was an important motivator to law and public politics which has the elders as the main focus. The laws coming from the demands of the elders and their representatives, considered as citizenship aquisition, are not always respected. The cultural aspects, the stereotypes and the almost total absence of representativity can be considered as the responsible for the lack of resistance to the usage of the amount of money raised by the Welfare State to assist people in the situation of necessity, inherent to the human being.